Registration-based methods applied to serial high-resolution T1-weighted magnetic resonance imaging for the assessment of brain volume changes in anorexia nervosa of the restricting type. (30th September 2018) - Santos, Mariana; Osório, Eva; Finnegan, Sarah; Clarkson, Matt; Timóteo, Sertório; Brandão, Isabel; Roma-Torres, António; Fox, Nick C.; Bastos-Leite, António J.
Highlights: Registration-based methods applied to serial high-resolution T1-weighted magnetic resonance imaging can be used to assess brain volume changes in patients with anorexia nervosa (AN). Brain volume changes were found to be strongly associated with variations in the body mass index of patients with AN of the restricting type. Therefore, assessments of brain volume change may become an additional measure of AN severity. Abstract: We aimed to determine whether variation in the body mass index (BMI)—a marker of anorexia nervosa (AN) severity—is associated with brain volume changes longitudinally estimated using registration-based methods on serial high-resolution T1-weighted magnetic resonance images (MRI). Fifteen female patients (mean age = 21 years; standard deviation [SD] = 5.7; range: 15–33 years) with the diagnosis of AN of the restricting type (AN-r)—according to the Diagnostic and Statistic Manual of Mental Disorders, 5 th edition criteria—underwent T1-weighted MRI at baseline and after a mean follow-up period of 11 months (SD = 6.4). We used the brain boundary shift integral (BSI) and the ventricular BSI (VBSI) to estimate volume changes after registering voxels of follow-up onto baseline MRI. Very significant and strong correlations were found between BMI variation and the brain BSI, as well as between BMI variation and the VBSI. After adjustment for age at onset, duration of illness, and the BMI rate of change before baseline MRI, the statistical significance of both associations persisted. Registration-based methods on serial MRI represent an additional tool to estimate AN severity, because they provide measures of brain volume change strongly associated with BMI variation.